1998
DOI: 10.1099/00221287-144-11-3019
|View full text |Cite
|
Sign up to set email alerts
|

A lipid A-associated protein of Porphyromonas gingivalis, derived from the haemagglutinating domain of the RI protease gene family, is a potent stimulator of interleukin 6 synthesis

Abstract: There is evidence that the lipid A-associated proteins (LAPs) of enteric bacteria can induce the synthesis of interleukin 1 (IL-1) and therefore may be important virulence factors. Porphyromonas gingivdis is now recognized as a major pathogen in the chronic inflammatory periodontal diseases and it has previously been reported that a crude LAP fraction from this organism could induce IL-1 and interleukin 6 (IL-6) synthesis. In the present study the chemical and biological properties of the LAPs of this bacteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…The activation of NF-B and mitogen-activated protein kinases such as ERK and p38 is known to be associated with upregulation of proinflammatory cytokine gene expression. In this context, Sharp et al (45) reported that lipid A-associated proteins of P. gingivalis have the ability to induce interleukin-6 (IL-6) in human monocytes and that the active component in the lipid A-associated proteins is HbR. These findings indicate that HbR may induce various cytokines from bone marrow macrophages.…”
Section: Discussionmentioning
confidence: 90%
“…The activation of NF-B and mitogen-activated protein kinases such as ERK and p38 is known to be associated with upregulation of proinflammatory cytokine gene expression. In this context, Sharp et al (45) reported that lipid A-associated proteins of P. gingivalis have the ability to induce interleukin-6 (IL-6) in human monocytes and that the active component in the lipid A-associated proteins is HbR. These findings indicate that HbR may induce various cytokines from bone marrow macrophages.…”
Section: Discussionmentioning
confidence: 90%
“…HbR, a 19-kilodalton protein, was intragenically encoded by an arginine-specific cysteine proteinase (Arg-gingipain, RGP)-encoding gene (rgpA), a lysine-specific cysteine proteinase (Lys-gingipain, KGP)-encoding gene (kgp), and a hemagglutinin (HA)-encoding gene (hagA) (11). Several pieces of evidence show that HbR forms a large proteinase-adhesin complex with RGP, KGP, and HA proteins that are encoded intragenically by these genes (12,13), and appears to be associated with a lipid A portion of lipopolysaccharide (LPS) (14). P. gingivalis has another RGP-encoding gene (rgpB); however, it does not encode HbR or HA (15).…”
mentioning
confidence: 99%
“…Kgp-associated HA2 may also function to stabilize or anchor this cell surface coating. In this context, HA2 has also been reported to function as a lipid A binding peptide with the potential to anchor gingipains and HagA into the outer membrane [29]. Alternatively, heme might be exchanged between heme-loaded Kgp and other Hb-receptor proteins or hemophores such as HagA for uptake or cell surface storage.…”
Section: Discussionmentioning
confidence: 98%